1982
DOI: 10.1104/pp.70.4.943
|View full text |Cite
|
Sign up to set email alerts
|

Isocitrate Lyase from Flax

Abstract: (3), and a variety of nematodes (2,10,22). In spite of its central importance in seedling metabolism and development, little is known about catalysis by plant isocitrate lyase.The first isolation of isocitrate lyase from plants was described by Khan et al. (23). Several molecular properties of the enzyme from flax were characterized but data were insufficient to deduce the kinetic mechanism. Moreover, nothing was reported about the structure of the active site. Information about these characteristics of the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…are inconsistent with the ordered mechanism (glyoxylate binding first) that has been proposed for other isocitrate lyases [21,29,30]. The ordered mechanism predicts that phosphoenolpyruvate should be an uncompetitive inhibitor with respect to glyoxylate.…”
Section: Kinetic Mechanism Of Isocitrate Lyasementioning
confidence: 79%
See 2 more Smart Citations
“…are inconsistent with the ordered mechanism (glyoxylate binding first) that has been proposed for other isocitrate lyases [21,29,30]. The ordered mechanism predicts that phosphoenolpyruvate should be an uncompetitive inhibitor with respect to glyoxylate.…”
Section: Kinetic Mechanism Of Isocitrate Lyasementioning
confidence: 79%
“…creased with pH in the neutral pH range, being 63 + 4 /tM hanism of E. coli isocitrate lyase is thus (n = 4) at pH 7.3, 32 + 5 /tM (n = 3) at pH 6.8 and 7 ,tM ordered mechanism reported for this (single determination) at pH 6.3. As has been shown for udomonas indigofera and Neurospora isocitrate lyase from other sources [33,34], the interthe enzyme from Linum usitatissimum actions of other effectors with isocitrate lyase were also inhibition patterns given by succinate, markedly dependent on pH; for example, the K, for hosphoenolpyruvate were similar to phosphoenolpyruvate in the cleavage reaction was , even though the authors favoured 0.91 mm at pH 7.3, but only 0.1 mm at pH 6.8, and the der mechanism [30]. Phosphoenol-corresponding values for succinate were 1.12 mm and Libitor of all the isocitrate lyases that 0.3 mM.…”
Section: Kinetic Mechanism Of Isocitrate Lyasementioning
confidence: 92%
See 1 more Smart Citation
“…2 (-). Km values for DS-isocitrate were obtained in this study (d) (flax), it was part of the glyoxylate subsite [18,21]. Nevertheless, the results suggested that bromopyruvate acts as an affinity labelling reagent for isocitrate lyase.…”
Section: Stoichiometry and Site Of Modification By Iodoacetatementioning
confidence: 85%
“…Several studies have identified possible active-site residues in ICL which may be important in catalysis and/or substrate binding. Inhibition of ICL from several organisms with diethyl pyrocarbonate (DEPC) [13][14][15] or Rose Bengal [16,17] implicated an active-site histidine residue. Ko et al [18] identified two histidine residues in the E. coli enzyme which reacted with DEPC, namely histidine-266 and histidine-306.…”
Section: Introductionmentioning
confidence: 99%